(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article examines the issues of the economic nature of globalization, its positive and negative consequences for the economy and social structure. The socio-cultural consequences of labor migration as one of the main manifestations of globalization are considered and ways to reduce the negative consequences of globalization are proposed.